Immunoglobulin A protease activity of Ureaplasma urealyticum. - Robertson, J A (1984)
All of 14 serotype standards and 34 of 35 wild-type strains of Ureaplasma urealyticum isolated from humans demonstrated an immunoglobulin A (IgA) protease activity. This activity degraded radiolabeled human IgA including IgA1 but not IgG or azocasein. The IgA fragments were detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, followed by radioautography, and they had molecular weights of about 110,000 and 50,000. The IgA protease activity persisted in 25 mM EDTA but was sensitive to trypsin; it was presumed to be protein. This is the fourth microbial genus and the first myocoplasma species in which an IgA protease activity has been identified. Such activity was absent in Mycoplasma pneumoniae, Mycoplasma hominis, and Acholeplasma laidlawii.